2008
DOI: 10.1038/mt.2008.197
|View full text |Cite
|
Sign up to set email alerts
|

Direct Muscle Delivery of GDNF With Human Mesenchymal Stem Cells Improves Motor Neuron Survival and Function in a Rat Model of Familial ALS

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease in which there is a progressive loss of motor neurons and their connections to muscle leading to paralysis. To maintain muscle connections in a rat model of familial ALS, we performed intramuscular transplantation with human mesenchymal stem cells (hMSC) as “Trojan horses” to deliver growth factors to the terminals of motor neurons as well as the skeletal muscles. hMSC engineered to secrete glial cell line derived neurotrophic factor (hMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(214 citation statements)
references
References 52 publications
6
206
1
1
Order By: Relevance
“…In this study, human MSCs (hMSC) isolated from neonatal bone marrow and transduced with LV encoding GDNF were transplanted into the skeletal muscle of a SOD1-G93A rat model. This work showed a neuroprotective effect, with an increase by 18 days in the lifespan, as well as a reduction in both degeneration of motor neurons in the spinal ventral horn and denervation of neuromuscular junctions [86]. The same research group reported in 2013 that the engineering of hMSCs to ectopically express both VEGF and GDNF could delay the onset of the disease by 6 days and more relevantly could prolong the lifespan of SOD1-G93A rats by 28 days, with the dual neurotrophic factors showing a synergistic effect in the maintenance of spinal motor neurons and neuromuscular junctions [84].…”
Section: Delivery Of Neurotrophic Factors For Alsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, human MSCs (hMSC) isolated from neonatal bone marrow and transduced with LV encoding GDNF were transplanted into the skeletal muscle of a SOD1-G93A rat model. This work showed a neuroprotective effect, with an increase by 18 days in the lifespan, as well as a reduction in both degeneration of motor neurons in the spinal ventral horn and denervation of neuromuscular junctions [86]. The same research group reported in 2013 that the engineering of hMSCs to ectopically express both VEGF and GDNF could delay the onset of the disease by 6 days and more relevantly could prolong the lifespan of SOD1-G93A rats by 28 days, with the dual neurotrophic factors showing a synergistic effect in the maintenance of spinal motor neurons and neuromuscular junctions [84].…”
Section: Delivery Of Neurotrophic Factors For Alsmentioning
confidence: 99%
“…Some studies have reported the efficacy of using MSCs to overexpress different neurotrophic factors, which can be used as an ex-vivo gene therapy tool in ALS models [84,86,95]. A major milestone was reached in 2009 when Suzuki et al demonstrated the efficacy of this method [86]. In this study, human MSCs (hMSC) isolated from neonatal bone marrow and transduced with LV encoding GDNF were transplanted into the skeletal muscle of a SOD1-G93A rat model.…”
Section: Delivery Of Neurotrophic Factors For Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits in survival are also noted when cells modified to secrete GDNF are injected in mutant SOD1 rodent models. Interestingly, implantation of human MSCs engineered to secrete GDNF into skeletal n/a n/a n/a n/a muscle were also able to support MN survival in the spinal cord [39], with synergistic effects attributed to vascular endothelial growth factor (VEGF) production [101]. Therefore, the ability of surrounding non-neuronal cells in the spinal cord and at the neuromuscular junction appears to play an important role in ALS pathogenesis, and the properties of stem cells are thereby ideally suited to achieve the goal of modulating the MN microenvironment.…”
Section: Transitioning From Early Preclinical Studies To Current Tranmentioning
confidence: 99%
“…The Stem cell therapies (SCT) have proven beneficial influence in all affected neural tissues leading to motoneurons regeneration [41][42][43][44], astrocytes replacement that slows motoneuron loss with a consequent survival increase [45], microglia regeneration [46,47] and growth factors secretion that promotes maintenance of motoneurons [48,49]. The effects seemed to be greater when the SCs delivery is intrathecal (IT) [50] or intramuscular (IM) [51].…”
Section: Stem Cell Therapy and Alsmentioning
confidence: 99%